THE IMPACT OF IJEPA POLICY ON THE VOLUME OF INDONESIAN BANANA EXPORTS TO JAPAN - Bimantara, I Kadek Rizky; Ayuningsasi, Anak Agung Ketut (Buletin Studi Ekonomi; VOLUME.30.NO.01.TAHUN.2025, 2025)
Economic relations between countries are an important factor that influences the economic development of each country. The potential country for Indonesia's banana exports is Japan. In order to facilitate international trade, an international trade agreement was made between Indonesia and Japan known as the Indonesia-Japan Economic Partnership Agreement (IJEPA). This research was conducted in Indonesia and Japan with a total of 29 years of observations obtained from secondary data, namely the Central Statistics Agency, UN Comtrade, and the World Bank. This study used linear regression analysis to determine the relationship between variables and was supported by SPSS applications. The results showed that Indonesia's banana production and IJEPA policy partially had a positive and significant effect, then the dollar exchange rate partially had a negative and significant effect, while Japan's GDP did not have a significant effect on Indonesia's banana export volume. Based on the results obtained, the government is expected to multiply similar agreements and improve regulations that can hinder the pace of exports. In addition, the government and stakeholders are expected to provide support facilities to exporters, which can later help improve Indonesia's export performance.